Los numerales ibéricos y el vascoiberismo (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
In this work we examine the implications of the existence of a great coincidence between the Iberian lexical numerals and the Basque ones, thus applying this proposal to the Iberian led of Ensérune, where we can observe that the possible lexical and morphological coincidences between both languages are not limited to the numeral system. Besides, some possible loan words from Greek to Iberian are proposed, and some aspects of the structure of the Iberian numeral system are revised.
Keywords: Iberian Language; Greek Language; Iberian Epigraphy; Iberian Numerals; Loan Words